PENGARUH PENDAPATAN SEKTOR PARIWISATA TERHADAP PENDAPATAN ASLI DAERAH (PAD) PADA KABUPATEN KUTAI KARTANEGARA - Insak, Novia Rabiâ€™ul (EKONOMIA, 2013)
NOVIA RABIâ€™UL INSAK , Faculty of Economics, University August 17, 1945 Samarinda 2013. The Effect Of Tourism Sector local revenue (PAD) At Kutai Kartanegara regency ( under the guidance ofÂ  Mrs. Titin Ruliana and Mr. Heriyanto )The hypothesis proposed is suspected that the " income effect of the Tourism Sector Percentage Of Revenue ( PAD ) At Kutai Kartanegara regency from 2007 to 2012 has increased . â€œReceivedâ€ , by reason of the regression coefficient increase in tourism revenue forÂ  0309 , or 30.9 % . Can significantly increase revenue ( PAD ) in Regency Kutai Kartanegara .Correlation coefficient of 0.243 , the Sig value of 0.00 . Smaller than the alpha (0.05) , a significant correlation coefficient . Model summary looks coefficient of 0.493 , and a coefficient of determination of 0.243 . To see significant determination comparing the calculated F value of 18.947 with the F table value of 4.00 ( table F with v1 = and v4 = 4 ) and compared between the Sig with alpha (5 %). Calculated F value is greater than the F table and the Sig smaller than alpha , then reject the conclusion significant mean coefficient of determination . The average increase in tourism sector revenues in 2007 s / d 2012 is 4.0 E +008 (404713387.082) with a standard deviation 1151387403.2 . While the average revenue (PAD) is 6.3 E +008 (625845024.918) with a standard deviation 1836922658.7 . Regression coefficient constant value of 2.1 E +008 ( 211,307,410.6812 ) with t count of 1.545 and 0.128 for the sig . Slope coefficient revenue (PAD) of 0.309 with a t value of 43.53 and a sig ofÂ  0.00 . T table value for this test is obtained by 2.02 alpha 5 % and df for 6 (n -1) , seen the value of t is greater than t table , and more besardari sig at 5 % alpha , then conclusions that can be drawn is rejecting significant meaning localrevenue constant coefficients (PAD) .